0773 When CPAPs are in Short Supply: A Review of Other FDA Approved OSA Interventions. (25th May 2022) - Zamora, Tania; Deering, Sean; Stepnowsky, Carl
Abstract: Introduction: The CPAP recall of 2021 has highlighted an inherent problem that occurs when a field of medicine is overly dependent on a single class of medical devices to treat a condition. The global shortage of CPAP devices has led to numerous individuals with OSA being unable to obtain a CPAP machine to treat their condition, including those with severe OSA. CPAP is well known to be efficacious in treating OSA, but has limited effectiveness, particularly for mild-to-moderate cases. It has been reported that there are nearly 200 different medical devices approved by the FDA to treat OSA. The goal of this project was to search the FDA databases to investigate the number of devices currently on file with the FDA. A secondary goal was to examine the range of FDA product categories for the treatment of OSA. Methods: An FDA database (AccessGUDID; https://accessgudid.nlm.nih.gov ) with a release date of December 1, 2021 was searched for devices that are approved for the treatment of sleep apnea. The text string "sleep apnea" was used for the search. Diagnostic devices, duplicate versions of the same treatment devices, and device accessories were excluded from the total counts. The FDA classifies medical devices into three categories (I, II, III), with a higher classification level indicating greater risk to patients. Results: The FDA AccessGUDID database search returned 166 results, which resulted in 72 unique devices across 10 product code categories. 9 of the 10 product codes in the FDA database were class II (medium risk) and 1/10 was classified as III (high risk). 65 of the devices were reported to be in commercial distribution at the time of the search and 7 were not. Conclusion: This analysis found that a relatively large number of FDA-approved devices exist for the treatment of OSA across a range of product categories. The field is encouraged to develop a better understanding of which subgroups of OSA patients could benefit from alternative forms of treatment in an effort to diversify treatment options and reduce the field's reliance on a single type of device, particularly for patients with mild-to-moderate OSA. Support (If Any): VA IIR 16-277